Challenges in pain assessment and management among individuals with intellectual and developmental disabilities. (16th July 2020) - Barney, Chantel C.; Andersen, Randi D.; Defrin, Ruth; Genik, Lara M.; McGuire, Brian E.; Symons, Frank J.
Abstract : Pain is common for individuals with intellectual and developmental disabilities, and we need to accelerate the use of evidence-based approaches to assess and manage pain. Abstract: Introduction: Intellectual and developmental disabilities (IDD) include conditions associated with physical, learning, language, behavioural, and/or intellectual impairment. Pain is a common and debilitating secondary condition compromising functional abilities and quality of life. Objectives: This article addresses scientific and clinical challenges in pain assessment and management in individuals with severe IDD. Methods: This Clinical Update aligns with the 2019 IASP Global Year Against Pain in the Vulnerable and selectively reviews recurring issues as well as the best available evidence and practice. Results: The past decade of pain research has involved the development of standardized assessment tools appropriate for individuals with severe IDD; however, there is little empirical evidence that pain is being better assessed or managed clinically. There is limited evidence available to inform effective pain management practices; therefore, treatment approaches are largely empiric and highly variable. This is problematic because individuals with IDD are at risk of developing drug-related side effects, and treatment approaches effective for other populations may exacerbate pain in IDD populations. Scientifically, we are especially challenged by biases in self-reported and proxy-reported pain scores, identifying valid outcome measures for treatment trials, being able to adequately power studies due to small sample sizes, and our inability to easily explore the underlying pain mechanisms due to compromised ability to self-report. Conclusion: Despite the critical challenges, new developments in research and knowledge translation activities in pain and IDD continue to emerge, and there are ongoing international collaborations.